PENINGKATAN KEMAMPUAN REPRESENTASI MATEMATIS MELALUI PEMBELAJARAN KONTEKSTUAL SISWA KELAS VIII SMP - Ahmad Rustam; Sardin Sardin (Universitas PGRI Adi Buana Surabaya, 2018)
This research is an experimental research with the aim to know: (1) improvement of the average of mathematical representation skills of class VIII student of SMP Negeri 2 Uluiwoi before getting learning with contextual approach; (2) improvement of the average of mathematical representation skills of grade VIII student of SMP Negeri 2 Uluiwoi before getting learning with conventional approach; (3) an average increase in student representation skills taught by a contextual learning approach is better than an increase in the average of mathematical representation skills taught by conventional learning. The population in this study is all students of class VIII SMP Negeri 2 Uluiwoi academic year 2016/2017 spread in 2 parallel classes with the number of 46 people. The population consists of two classes, then the sample is chosen by specifying the first class as the experimental class and the second class as the control class, assuming that the two classes are statistically homogeneous. This data collection technique uses test and observation techniques. Data analysis techniques use descriptive statistics and inferential statistics. The results of empirical research indicate that; (1) Improvement of mathematical representation skills of class VIIIA students taught by using contextual learning model consisting of 24 students showed average value 46,25 and deviation standard 7,409 with mean increase or average N-Gain value 0, 42 is in the medium category. The improvement of the mathematical representation skills of VIIIB class students taught by using conventional learning model which consist of 22 students shows the average value 49,09 and deviation standard 15,402 with mean increase or average of N-Gain value equal to 0,25 is at low category. Inferential statistical analysis shows that (1) there is an increase in the average ability of students 'mathematical representation after having contextual learning, (2) There is an increase in the average ability of students' mathematical representation after conventional learning, and (3) students' mathematical representation with the application of contextual approach is higher than the conventional learning model in Grade VIII students of SMP Negeri 2 Uluiwoi. Keywords: Improved, Contextual, Conventional, N-Gain, mathematical representation skills.